Enhancement of Hyphae Growth and Medium Optimization for Pleurotus eryngii-3 under Submerged Fermentation - Changqing Liu; Jiajie Feng; Simin Wang; Yi Cao; Yuxiang Shen (Agronomy, 2022)
There are a variety of amino acids and polysaccharides contained in Pleurotus eryngii that can improve immunity and prevent cancer in humans. The purpose of this research was to investigate the improved quality hypha of P. eryngii-3, which could shorten the ripening cycle of the hypha and increase economic benefits to industries. In this paper, the quality hypha of P. eryngii-3 was investigated for the DCW, total protein, polysaccharides, laccase activity, and so on. The medium was screened and carbon and nitrogen sources were screened and optimized as 40 g/L of corn flour and soybean meal by P. eryngii-3. Then, the effects of pH, temperature, volume, and rotation speed were investigated, in which the suitable fermentation conditions were, respectively, pH = 6, a temperature of 27 °C, 90 mL of fermentation broth, and a 150 r/min rotation speed. Meanwhile, the transcription levels of Lcc1, Lcc5, Lcc8, and Lcc12 were upregulated by 10.25-, 3.32-, 2.33-, and 6.29-fold, respectively, after the optimization. In addition, the response surface method of the BBD was utilized for further improvements to the DCW by P. eryngii-3, in which the optimized DCW reached 17.2345 ± 0.7845 g/L.